Mystery Science Theater 3000 presents. Werewolf [videorecording (DVD)] - Murphy, Kevin, 1956-; Nelson, Michael J.; Corbett, Bill; Brantseg, Patrick (Mystery Science Theater 3000 20th Anniversary edition., 2008)
From the seventh season of Mystery Science Theater 3000, Mike and his robot friends add their comments to the film Werewolf. In the film itself, a workman at an archaeological dig in Arizona is accidentally injured by the skeletal remains of what is believed to be a werewolf. Within hours, he begins showing the signs of becoming a werewolf, prompting his foreman to begin conspiring to create a werewolf of his own.